Exploring Design towards a Sustainable City: Through the lens of Cape Town as World Design Capital 2014 - Naidoo, Marjorie Lanette (Stellenbosch : Stellenbosch University, 2016)
Thesis (MPA)--Stellenbosch University, 2016.